Case Report: Novel Copy Number Variant 16p11.2 Duplication Associated With Prune Belly Syndrome - Talluri, Sriharsha; Goedde, Michael A.; Rosenberg, Eran; Canalichio, Katie L.; Peppas, Dennis; White, Jeffrey T. (Frontiers in Pediatrics, 2021)
Prune belly syndrome (PBS) is a rare congenital disease that predominantly occurs in males and is identified by its classic triad of abdominal wall musculature deficiencies, cryptorchidism, and urinary tract abnormalities. However, numerous anomalies involving the kidneys, heart, lungs, and muscles have also been reported. A multitude of chromosomal abnormalities have been implicated in its pathogenesis. PBS can occur in association with trisomy 18 and 21. Gene duplications and deletions have also been reported; however, a definite cause of PBS is still unknown. We report the first PBS patient with a copy number variant in 16p11.2.